A cardiopulmonary resuscitation guide for healthcare providers - Mohamed, Rozilah @ Abdul Hadi; Osman, Ariff; Md Ralib, Azrina; Mat Nor, Mohd Basri; Lukman, Mohd Fahmi; Ismail, Mohd Nizamuddin; Abdul Ghani, Muhamad Rasydan; Ramly, Nur Fariza; Nanyan, Suhaila (Department of Anaesthesiology & Intensive Care, Kulliyyah of Medicine, International Islamic University Malaysia, 2018)
Cardiopulmonary resuscitation or CPR is the term used to describe a series of action that comprises of artificial respiration and chest compressions to patients in cardiorespiratory arrest. It has to be initiated promptly to improve the chance of survival before advanced medical care is available. CPR is an important clinical skill, almost mandatory for every healthcare personnel. The CPR procedure is an essential component of Basic Life Support (BLS) and Advanced Cardiac Life Support (ACLS). This book covers the important aspects of Basic Life Support (BLS) and serves as a guide to participants of the CPR course. Participants are required to read this book before attending the course. Its main objective is to provide a simple and comprehensive reference to participants of our CPR workshops. It has been updated according to the latest 2015 guidelines published by recognised bodies such as The International Liaison Committee on Resuscitation (ILCOR), and the American Heart Association (AHA). We have also incorporated a chapter on Islamic Ethics, in line with the IIICE (Integration, Islamisation, Internationalisation and Comprehensive Excellence) mission of our university.